Decreasing the acid value of pyrolysis oil via esterification using ZrO2/SBA-15 as a solid acid catalyst. (February 2020) - Li, Lu; Yan, Bin; Li, Huaxiao; Yu, Shitao; Ge, Xiaoping
Abstract: The high acid value of pyrolysis oil obtained from biologic oil is the main drawback that not only affects the properties of pyrolysis oil, but also leads to the corrosion of equipment. Herein, pyrolysis oil obtained from rubber seed oil was upgraded via esterification using ZrO2 /SBA-15 as a solid acid catalyst. Using ZrO2 /SBA-15 as a catalyst, the acid value of the esterified pyrolysis oil obtained from rubber seed oil was only 1.2 mg KOHg −1 . The density and kinematic viscosity both reached the standard range of 0 # diesel oil. The excellent catalytic activity of ZrO2 /SBA-15 was studied using NH3 -TPD and Py-IR. Furthermore, the conversion reached 96.7% when the ZrO2 /SBA-15 catalyst was re-used three times, which shows the ZrO2 /SBA-15 catalyst possessed excellent catalytic activity and stability for upgrading pyrolysis oil via esterification. Highlights: Pyrolysis oil of rubber seed oil (RSO) was upgraded. Methyl esterification of pyrolysis oil using ZrO2 /SBA-15 as catalyst. The obtained biofuel was of low acid value. ZrO2 /SBA-15 is of excellent catalytic activity and stability.